On the issue of legal regulation of quarantine and plant protection in agriculture - Saskevich, Veranika V. (Journal of the Belarusian State University. Law, 2024)
The article is devoted to the analysis of the legislation on quarantine and plant protection. The characteristics of the state of legal regulation are given, taking into account its latest changes. The close connection between the supranational and national levels of sources of law aimed at ensuring phytosanitary safety is emphasised. Positive and negative trends in the development of legal regulation have been identified, namely consistent legal support for digitalisation in crop production, ignoring individuals as participants in relations in the field of quarantine and plant protection, simplifying requirements in the field of trade and use with plant protection products. The need to supplement and clarify the correlation of key legal categories is substantiated. The conclusion is argued about the need to specify the legislative framework for regulating relations in the field of quarantine and plant protection with the participation of individuals.
Keywords: legal regulation of quarantine and plant protection; regulations on the use of pesticides; agricultural legislation; agricultural law